Variographic analysis to evaluate the coverage area of a wireless system at 5.8 GHz band in a region of oil fields. Issue 11 (1st May 2019) - Fialho, B.R.; Andrade, H.D.; Fontgalland, G.; Paiva, J.L.S.; Queiroz, I.S.
Abstract : The advancement of embedded technologies has led to increasing demand for bandwidth in telecommunications solutions, this increased the researches related to the architecture of wireless networks and applied electromagnetism. In view of this, the digital transceiver radios need an adequate received signal strength indicator to enable the traffic of information by the radio propagation channel and to provide quality in the data network for the users to exercise the operational activities. The objective of this Letter is to perform the exploratory and variographic analysis of the data collected in the oil fields. Hence, evaluate the behaviour of the surface power distribution received from a wireless system in the frequency range of 5.8 GHz located in the well‐automation region called Canto do Amaro, Brazil, where there are frequent communications failures for mobile stations. With the data measured in the measurement campaigns, variogram models were constructed and compared for the construction of interpolation matrices and contour maps, with these results the precision criteria of the kriging methods employed in the study region were established.